2007
DOI: 10.1016/j.psyneuen.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in ACTH pulsatility following metyrapone blockade in patients with major depression

Abstract: SummaryNumerous studies suggest that increased central drive to the hypothalamic-pituitary adrenal axis occurs in patients with major depression. To determine if increased central drive occurs throughout the 24H, we evaluated ACTH secretion under metyrapone blockade of cortisol production. We collected blood every 10 minutes for measurement of ACTH and data were analyzed for ACTH pulsatility using the pulse detection algorithm deconvolution. We studied 28 patients with major depression and 28 age and sex match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Although deficits in HPA axis function are a hallmark of MDD (Gibbons and McHugh, 1962;Carroll et al, 1976a, b;Nemeroff et al, 1984;Arborelius et al, 1999;Webster et al, 2002;Parker et al, 2003;Holsen et al, 2013), gonadal hormone deficits are also evident Schmidt, 1996, 2006;Young et al, 2000Young et al, , 2007Himelein and Thatcher, 2006;Young and Korszun, 2002;Graziottin and Serafini, 2009; for a review, see Goldstein et al, 2014). For example, women with persistent MDD have twice the risk of early perimenopausal transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although deficits in HPA axis function are a hallmark of MDD (Gibbons and McHugh, 1962;Carroll et al, 1976a, b;Nemeroff et al, 1984;Arborelius et al, 1999;Webster et al, 2002;Parker et al, 2003;Holsen et al, 2013), gonadal hormone deficits are also evident Schmidt, 1996, 2006;Young et al, 2000Young et al, , 2007Himelein and Thatcher, 2006;Young and Korszun, 2002;Graziottin and Serafini, 2009; for a review, see Goldstein et al, 2014). For example, women with persistent MDD have twice the risk of early perimenopausal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the lifecourse, changes in women's reproductive status have been associated with increased risk for mood disturbance and MDD (Rabin et al, 1990;Baischer et al, 1995;Schmidt, 1996, 2006;Harlow et al, 2003;Payne, 2003;Roca et al, 2003;Spinelli, 2005;Payne et al, 2009;Freeman et al, 2014). MDD incidence increases with pubertal onset in females (Angold and Costello, 2006), chronic use of oral contraceptives (Young et al, 2007), the postpartum period (Bloch et al, 2000;Brummelte and Galea, 2010), and perimenopause (Schmidt and Rubinow, 2009). A recent longitudinal population-based study of women found that the risk of depressive symptoms dropped significantly following menopause.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one study using stressors that are etiologically related to affective disorders showed that women responded to social rejection with greater salivary-free cortisol than men (25). Furthermore, depressed women exhibit greater ACTH secretion in the evening compared with depressed men (26,27). Thus, women may have a distinct type of HPA axis sensitivity that is related to the vulnerability to affective disorders.…”
mentioning
confidence: 99%
“…It was further demonstrated that male subjects had a greater HPA axis response to a psychological stressor than female subjects, whereas women had a greater hormonal reactivity to pharmacologic stimulation [26] . Sex differences in ACTH pulsatility following metapyrone blockade were observed in another study, with men showing smaller ACTH AUCs than women [27] . The fact that highly anxious females exhibited lower cortisol release than highly anxious males further suggested that high trait anxiety females may be associated with an inability to respond with sufficient activation of the HPA axis under acute psychological stress [28] .…”
Section: Discussionmentioning
confidence: 71%